Biomass loaded metal nano composite catalyst as well as preparation method and application thereof
By using biomass-loaded metal nanocomposite catalysts, the problem of difficult degradation of azo dyes is solved, efficient degradation is achieved, and it has good recycling performance, reducing the cost of using the catalyst.
Patent Information
- Application Number
- CN202411303069.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-21
AI Technical Summary
Azo dyes are difficult to degrade naturally in water bodies, resulting in damage to the water ecosystem and are harmful to teratogenic, carcinogenic and mutation-induced. The degradation efficiency in the prior art is low.
Using a biomass-loaded metal nanocomposite catalyst, the biomass material is mixed with a polyethyleneimine solution and cross-linked and polymerized, and then a metal salt solution is added for adsorption, and a reduction reaction is performed in the reducing agent solution to prepare the biomass-loaded material. Metal nanocomposite catalysts. The catalyst reacts with azo dye wastewater after mixing, and can effectively degrade azo dyes.
Under acidic conditions, biomass load metal nano -composite catalysts have excellent degradation effects on puppet nitrogen dyes, the degradation rate can reach 100 %, and it has good circulating performance, which can reduce the cost of catalyst to a certain extent.
Smart Images

Figure CN119327509A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of azo dye degradation, and in particular to a biomass-loaded metal nanocomposite catalyst and a preparation method and application thereof. Background Art
[0002] Azo dyes are the most widely used dyes in industries such as printing, textiles, and papermaking. However, in actual use, about 20% of the dyes cannot be utilized and are discharged through wastewater. However, azo dyes have a complex structure, contain azo groups in their molecules, have high chemical stability, have a certain degree of light resistance and antioxidant ability in water, and are difficult to degrade naturally, which in turn causes damage to the aquatic ecosystem. In addition, azo dyes also have the "three-hazard" effects of teratogenicity, carcinogenicity, and mutagenicity, which seriously endanger human health. Therefore, it is of great significance to study a biomass-loaded metal nanocomposite catalyst and its preparation method and use it for the degradation of azo dyes. Summary of the invention
[0003] The purpose of the present invention is to provide a biomass-loaded metal nanocomposite catalyst and a preparation method and application thereof, so as to solve the problem of low degradation efficiency of azo dyes in the prior art.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a method for preparing a biomass-supported metal nanocomposite catalyst, comprising the following steps:
[0006] (1) mixing a biomass material and a polyethyleneimine solution and incubating the mixture, and then adding a glutaraldehyde solution for cross-linking polymerization to obtain a modified biomass material;
[0007] (2) adding the modified biomass material to a metal salt solution for adsorption to obtain a biomass material loaded with metal ions;
[0008] (3) The biomass material loaded with metal ions is dispersed in a reducing agent solution to carry out a reduction reaction, thereby obtaining a biomass loaded metal nanocomposite catalyst.
[0009] Preferably, in step (1), the mass ratio of the biomass material to the polyethyleneimine solution is 1 g:80-120 mL, wherein the mass concentration of the polyethyleneimine solution is 3%-10%.
[0010] Preferably, in step (1), the incubation temperature is 25 to 35° C., and the incubation time is 6 to 30 hours.
[0011] Preferably, in step (1), the mass ratio of the biomass material to the glutaraldehyde solution is 1:3-10, wherein the mass concentration of the glutaraldehyde solution is 5%-50%; the temperature of the cross-linking polymerization is 25-35°C, and the time of the cross-linking polymerization is 1-3h.
[0012] Preferably, in step (2), the metal salt in the metal salt solution comprises one or more of copper salt, iron salt, nickel salt, cobalt salt, gold salt, platinum salt, palladium salt and cerium salt; the concentration of the metal salt solution is 50 to 1000 mg / L; the adsorption time is 4 to 8 hours;
[0013] The mass volume ratio of the modified biomass material and the metal salt solution is 20-40 mg:10-1000 mL.
[0014] Preferably, in step (2), the reducing agent comprises one or more of sodium formate, sodium acetate, sodium borohydride, sodium sulfite and sodium thiosulfate; the concentration of the reducing agent solution is 1 to 50 mmol / L; the reduction reaction time is 10 to 180 min;
[0015] The mass volume ratio of the modified biomass material and the reducing agent solution is 20-40 mg:10-1000 mL.
[0016] The present invention provides a biomass-supported metal nanocomposite catalyst prepared by the above-mentioned method for preparing the biomass-supported metal nanocomposite catalyst.
[0017] The present invention provides an application of the above-mentioned biomass-loaded metal nanocomposite catalyst in the degradation of azo dyes, comprising the following steps: mixing azo dye wastewater and the biomass-loaded metal nanocomposite catalyst and reacting them.
[0018] Preferably, the concentration of azo dye in the azo dye wastewater is 5-50 mg / L; and the addition amount of the biomass-supported metal nanocomposite catalyst is 0.1-1 g / L.
[0019] Preferably, the reaction time is 10 to 60 minutes.
[0020] Beneficial effects of the present invention:
[0021] (1) The biomass-supported metal nanocomposite catalyst prepared in the present invention has an excellent degradation effect on the azo dye reactive black KN-B, and the degradation rate can reach 100% under acidic conditions.
[0022] (2) The biomass-loaded metal nanocomposite catalyst prepared by the present invention has good recycling performance. The degradation efficiency of the first cycle is recorded as 100%. After five cycles, the efficiencies of the modified microorganism-loaded palladium nanocomposite catalyst (Pd / MMR) and the modified microorganism-loaded platinum nanocomposite catalyst (Pt / MMR) are 95.64% and 96.47% of the first use, respectively. This shows that the biomass-loaded metal nanocomposite catalyst prepared by the present invention has good reusability and can reduce the use cost of the catalyst to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The Pd / MMR catalytic TMB oxidation activity comparison chart prepared in Examples 1 to 4, wherein (a) is the amount of palladium ion adsorption, (b) is the sodium formate concentration, and (c) is the reaction time;
[0024] Figure 2 SEM-EDS images of Pd / MMR prepared in Example 1 and Pd / UMR prepared in Comparative Example 1, wherein (a), (c) and (e) are electron microscope images, EDS element mapping images and EDS element distribution images of Pd / UMR, respectively, and (b), (d) and (f) are electron microscope images, EDS element mapping images and EDS element distribution images of Pd / MMR, respectively;
[0025] Figure 3 TEM images and electron diffraction images of Pd / MMR prepared in Example 1 and Pd / UMR prepared in Comparative Example 1, wherein (a) is a TEM image of Pd / UMR, (b) is a TEM image of Pd / MMR (inset: particle size distribution image of Pd / MMR), (c) is a TEM image of Pd / UMR (inset: electron diffraction image of Pd / UMR), and (d) is a TEM image of Pd / MMR (inset: electron diffraction image of Pd / MMR);
[0026] Figure 4 The XPS spectra of Pd / MMR prepared in Example 1 and Pd / UMR prepared in Comparative Example 1, wherein (a) is the full spectrum and (b) is the Pd 3d spectrum;
[0027] Figure 5 is the XRD pattern of Pd / MMR prepared in Example 1;
[0028] Figure 6 The Pt / MMR prepared in Examples 5 to 8 is a comparison chart showing the effect of the TMB oxidation activity on the catalysis, wherein (a) is the amount of platinum ion adsorption, (b) is the sodium borohydride concentration, and (c) is the reaction time;
[0029] Figure 7SEM-EDS images of the Pt / MMR prepared in Example 5 and the Pt / UMR prepared in Comparative Example 2, wherein (a), (c) and (e) are the electron microscope image, EDS element mapping image and EDS element distribution image of the Pt / UMR, respectively, and (b), (d) and (f) are the electron microscope image, EDS element mapping image and EDS element distribution image of the Pt / MMR, respectively;
[0030] Figure 8 TEM images and electron diffraction images of Pt / MMR prepared in Example 5 and Pt / UMR prepared in Comparative Example 2, wherein (a) is a TEM image of Pt / UMR, (b) is a TEM image of Pt / MMR (inset: particle size distribution diagram of Pt / MMR), (c) is a TEM image of Pt / UMR (inset: electron diffraction image of Pt / UMR), and (d) is a TEM image of Pt / MMR (inset: electron diffraction image of Pt / MMR);
[0031] Fig. 9 The XPS spectra of the Pt / MMR prepared in Example 5 and the Pt / UMR prepared in Comparative Example 2, wherein (a) is the full spectrum and (b) is the Pt4f spectrum;
[0032] Fig.10 XRD patterns of Pt / MMR prepared in Example 5 and Pt / UMR prepared in Comparative Example 2;
[0033] Fig.11 It is the linear relationship diagram between the concentration of reactive black KN-B and the absorbance value;
[0034] Fig.12 The graphs are the content curves of reactive black KN-B after reaction at different pH values in Application Example 2 and Application Example 5, wherein (a) is Application Example 2 and (b) is Application Example 5;
[0035] Fig.13 The comparison chart of the degradation rate of active black KN-B under different addition amounts of catalyst in Application Example 1 and Application Example 3, Application Example 4 and Application Example 6, wherein (a) is Application Example 1 and Application Example 3, and (b) is Application Example 4 and Application Example 6;
[0036] Fig.14 This is a comparison chart of the degradation efficiency of Pd / MMR used in Application Example 1 and Pt / MMR used in Application Example 4 after five cycles, where (a) is Pd / MMR and (b) is Pt / MMR. DETAILED DESCRIPTION
[0037] The present invention provides a method for preparing a biomass-supported metal nanocomposite catalyst, comprising the following steps:
[0038] (1) mixing a biomass material and a polyethyleneimine solution and incubating the mixture, and then adding a glutaraldehyde solution for cross-linking polymerization to obtain a modified biomass material;
[0039] (2) adding the modified biomass material to a metal salt solution for adsorption to obtain a biomass material loaded with metal ions;
[0040] (3) The biomass material loaded with metal ions is dispersed in a reducing agent solution to carry out a reduction reaction, thereby obtaining a biomass loaded metal nanocomposite catalyst.
[0041] In the present invention, the biomass material is preferably plant, animal, microbial biomass or derivatives thereof, more preferably fungus or plant, and more preferably yeast.
[0042] In the present invention, in the step (1), the mass ratio of the biomass material to the polyethyleneimine solution is 1g:80-120mL, preferably 1g:90-110mL, and more preferably 1g:100mL, wherein the mass concentration of the polyethyleneimine solution is 3%-10%, preferably 4%-8%, and more preferably 5%-7%.
[0043] In the present invention, in the step (1), the incubation temperature is 25 to 35°C, preferably 28 to 32°C, and more preferably 30°C, and the incubation time is 6 to 30 hours, preferably 10 to 26 hours, and more preferably 12 to 24 hours.
[0044] In the present invention, in the step (1), the mass ratio of the biomass material to the glutaraldehyde solution is 1:3-10, preferably 1:4-8, and more preferably 1:5-6, wherein the mass concentration of the glutaraldehyde solution is 5%-50%, and more preferably 25%; the temperature of the cross-linking polymerization is 25-35°C, preferably 28-32°C, and more preferably 30°C; the time of the cross-linking polymerization is 1-3h, preferably 1.5-2.5h, and more preferably 2h.
[0045] In the present invention, in the step (2), the metal salt in the metal salt solution comprises one or more of copper salt, iron salt, nickel salt, cobalt salt, gold salt, platinum salt, palladium salt and cerium salt, preferably one or more of nickel salt, platinum salt and palladium salt, more preferably platinum salt and palladium salt; the concentration of the metal salt solution is 50-1000 mg / L, preferably 300-800 mg / L, more preferably 500-700 mg / L; the adsorption time is 4-8 h, preferably 5-7 h, more preferably 6 h;
[0046] The mass volume ratio of the modified biomass material and the metal salt solution is 20-40 mg:10-1000 mL, preferably 25-35 mg:20-900 mL, and more preferably 30 mg:30-800 mL.
[0047] In the present invention, in the step (2), the reducing agent comprises one or more of sodium formate, sodium acetate, sodium borohydride, sodium sulfite and sodium thiosulfate, preferably sodium formate, sodium acetate or sodium borohydride, and more preferably sodium formate or sodium borohydride; the concentration of the reducing agent solution is 1 to 50 mmol / L, preferably 2.5 to 20 mmol / L, and more preferably 5 to 15 mmol / L; the reduction reaction time is 10 to 180 min, preferably 10 to 50 min, and more preferably 20 to 40 min;
[0048] The mass volume ratio of the modified biomass material and the reducing agent solution is 20-40 mg:10-1000 mL, preferably 25-35 mg:20-900 mL, and more preferably 30 mg:30-800 mL.
[0049] In the present invention, the reduction reaction is carried out in an inert atmosphere, wherein the inert atmosphere is preferably a nitrogen atmosphere or a helium atmosphere.
[0050] The present invention provides a biomass-supported metal nanocomposite catalyst prepared by the above-mentioned method for preparing the biomass-supported metal nanocomposite catalyst.
[0051] The present invention provides an application of the above-mentioned biomass-loaded metal nanocomposite catalyst in the degradation of azo dyes, comprising the following steps: mixing azo dye wastewater and the biomass-loaded metal nanocomposite catalyst and reacting them.
[0052] In the present invention, the concentration of azo dye in the azo dye wastewater is 5-50 mg / L, preferably 10 mg / L; the addition amount of the biomass-supported metal nanocomposite catalyst is 0.1-1 g / L, preferably 0.2-0.3 g / L, and more preferably 0.3 g / L.
[0053] In the present invention, after the azo dye wastewater and the biomass-supported metal nanocomposite catalyst are mixed, the pH value is preferably adjusted before reacting, and the adjusted pH value is 1.0 to 4.0, preferably 2.0 to 3.0, and more preferably 2.0.
[0054] In the present invention, the reaction time is 10 to 60 minutes, preferably 30 to 60 minutes.
[0055] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0056] In the embodiment of the present invention, Pichia pastoris residue is used. First, the Pichia pastoris residue is pretreated: the Pichia pastoris residue is washed with deionized water for 5 times to remove residual chemical reagents and metabolites, and then dried at 60° C. for 6 h, followed by grinding and passing through a 200-mesh sieve to obtain unmodified microbial residue (UMR), which is stored in a dry and sealed container for standby use.
[0057] Example 1
[0058] 1 g of UMR and 100 mL of polyethyleneimine solution (mass concentration of 5%) were mixed evenly, and incubated in a constant temperature incubator at a temperature of 30°C and a rotation speed of 150 rpm for 24 h. Then, 5 g of glutaraldehyde aqueous solution (mass concentration of 25%) was added, and the mixture was shaken in a constant temperature incubator at a temperature of 30°C and a rotation speed of 150 rpm for 2 h for cross-linking polymerization. After that, the mixture was centrifuged, washed with deionized water three times, freeze-dried at -50°C for 12 h, and ground and sieved through a 200-mesh sieve to obtain modified microbial residue (MMR). The structural formula of polyethyleneimine is shown below:
[0059]
[0060] 30 mg of MMR was added to 30 mL of palladium chloride solution (initial concentration was 570.83 mg / L), and then placed in a constant temperature incubator at a temperature of 25°C and a rotation speed of 150 rpm for adsorption for 6 hours, and then filtered through a 0.22 μm filter membrane to obtain a modified microbial residue loaded with palladium ions (the adsorption amount of palladium ions was 550 mg / g).
[0061] The modified microbial residue loaded with palladium ions was mixed with 30 mL of sodium formate solution (concentration of 7.5 mmol / L), nitrogen was introduced, and reduced at room temperature for 30 minutes. After the reduction reaction was completed, it was filtered again through a 0.22 μm filter membrane, and the membrane retentate was dried at 50°C to obtain a modified microbial residue loaded with palladium nanocomposite catalyst, recorded as Pd / MMR.
[0062] Example 2
[0063] The difference from Example 1 is that the initial concentrations of palladium chloride solution are 50.13 mg / L, 150.49 mg / L, 251.06 mg / L, 352.1 mg / L and 454.66 mg / L, respectively, and the corresponding adsorption amounts of palladium ions are 50 mg / g, 150 mg / g, 250 mg / g, 350 mg / g and 450 mg / g, respectively, and other conditions are the same.
[0064] Example 3
[0065] The difference from Example 1 is that the concentrations of the sodium formate solution are 2.5 mmol / L, 5 mmol / L, 10 mmol / L and 12.5 mmol / L, respectively, and other conditions are the same.
[0066] Example 4
[0067] The difference from Example 1 is that the reduction reaction time is 10 min, 20 min, 40 min and 50 min respectively, and the other conditions are the same.
[0068] Example 5
[0069] 1 g of UMR and 100 mL of polyethyleneimine solution (mass concentration of 5%) were mixed evenly, and the mixture was shaken in a constant temperature incubator at a temperature of 30°C and a rotation speed of 150 rpm for 24 hours for incubation. Then, 5 g of glutaraldehyde aqueous solution (mass concentration of 25%) was added, and the mixture was shaken in a constant temperature incubator at a temperature of 30°C and a rotation speed of 150 rpm for 2 hours for cross-linking polymerization. The mixture was then centrifuged, washed three times with deionized water, freeze-dried at -50°C for 12 hours, and ground and sieved through a 200-mesh sieve to obtain modified microbial residue (MMR).
[0070] 30 mg of MMR was added to 30 mL of platinum chloride solution (initial concentration was 400.65 mg / L), and then placed in a constant temperature incubator at a temperature of 25°C and a rotation speed of 150 rpm for adsorption for 6 hours, and then filtered through a 0.22 μm filter membrane to obtain modified microbial residue loaded with platinum ions (the adsorption amount of platinum ions was 350 mg / g).
[0071] The modified microbial residue loaded with platinum ions was mixed with 30 mL of sodium borohydride solution (concentration of 7.5 mmol / L), nitrogen was introduced, and reduced at room temperature for 20 minutes. After the reduction reaction was completed, it was filtered again through a 0.22 μm filter membrane, and the membrane retentate was dried at 50°C to obtain a modified microbial residue loaded with palladium nanocomposite catalyst, recorded as Pt / MMR.
[0072] Example 6
[0073] The difference from Example 5 is that the initial concentrations of the platinum chloride solution are 101.96 mg / L, 153.55 mg / L, 205.99 mg / L, 260.18 mg / L and 319.06 mg / L, respectively, and the corresponding adsorption amounts of platinum ions are 100 mg / g, 150 mg / g, 200 mg / g, 250 mg / g and 300 mg / g, respectively, and other conditions are the same.
[0074] Example 7
[0075] The difference from Example 5 is that the concentrations of the sodium borohydride solution are 2.5 mmol / L, 5 mmol / L, 10 mmol / L and 12.5 mmol / L, respectively, and the other conditions are the same.
[0076] Example 8
[0077] The difference from Example 5 is that the reduction reaction time is 5 min, 10 min, 30 min and 40 min respectively, and the other conditions are the same.
[0078] Comparative Example 1
[0079] 1 g of UMR was added to 30 mL of palladium chloride solution (initial concentration was 570.83 mg / L), and then placed in a constant temperature incubator at 25°C and 150 rpm for adsorption for 6 hours, and then filtered through a 0.22 μm filter membrane to obtain microbial residue loaded with palladium ions.
[0080] The microbial residue loaded with palladium ions was mixed with 30 mL of sodium formate solution (concentration of 7.5 mmol / L), nitrogen was introduced, and reduced at room temperature for 30 min. After the reduction reaction was completed, it was filtered again through a 0.22 μm filter membrane, and the membrane retentate was dried at 50°C to obtain a microbial residue-loaded palladium nanocomposite catalyst, recorded as Pd / UMR.
[0081] Comparative Example 2
[0082] 1 g of UMR was added to 30 mL of platinum chloride solution (initial concentration was 425 mg / L), and then placed in a constant temperature incubator at a temperature of 25°C and a rotation speed of 150 rpm for adsorption for 6 hours, and then filtered through a 0.22 μm filter membrane to obtain microbial residue loaded with platinum ions.
[0083] The microbial residue loaded with platinum ions was mixed with 30 mL of sodium borohydride solution (concentration of 7.5 mmol / L), nitrogen was introduced, and reduced at room temperature for 20 minutes. After the reduction reaction was completed, it was filtered again through a 0.22 μm filter membrane, and the membrane retentate was dried at 50°C to obtain a microbial residue-loaded platinum nanocomposite catalyst, recorded as Pt / UMR.
[0084] Application Example 1
[0085] 0.2 g of Pd / MMR prepared in Example 1 was added to 1 L of active black KN-B wastewater (the concentration of active black KN-B was 10 mg / L), the pH value was adjusted to 2, the reaction was carried out at room temperature for 30 min, and then the solid-liquid separation was carried out using 0.22 μm filter paper to test the concentration of active black KN-B in the liquid.
[0086] Application Example 2
[0087] Four 1L portions of reactive black KN-B wastewater (the concentration of reactive black KN-B was 10 mg / L) were prepared, 0.2 g of Pd / MMR prepared in Example 1 was added to each portion, the pH value was adjusted to 1, 2, 3 or 4, respectively, and the concentration of reactive black KN-B in the wastewater was tested at different reaction times (5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 40 min, 50 min, 60 min).
[0088] Application Example 3
[0089] The difference from Application Example 1 is that the added amounts of Pd / MMR prepared in Example 1 are 0.1 g and 0.3 g respectively, and other conditions are the same.
[0090] Application Example 4
[0091] 0.2 g of Pt / MMR prepared in Example 5 was added to 1 L of active black KN-B wastewater (the concentration of active black KN-B was 10 mg / L), the pH value was adjusted to 2, the reaction was carried out at room temperature for 30 min, and then the solid-liquid separation was carried out using 0.22 μm filter paper to test the concentration of active black KN-B in the liquid.
[0092] Application Example 5
[0093] Four 1L portions of reactive black KN-B wastewater (the concentration of reactive black KN-B was 10 mg / L) were prepared, 0.2 g of Pt / MMR prepared in Example 5 was added to each portion, the pH value was adjusted to 1, 2, 3 or 4, respectively, and the concentration of reactive black KN-B in the wastewater was tested at different reaction times (5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 40 min, 50 min).
[0094] Application Example 6
[0095] The difference from Application Example 4 is that the addition amounts of Pt / MMR prepared in Example 5 are 0.1 g and 0.3 g respectively, and other conditions are the same.
[0096] Calculate the degradation rate of reactive black KN-B using the following formula:
[0097]
[0098] In formula (1), C0 is the initial concentration of reactive black KN-B, C t is the concentration of reactive black KN-B at time t, and D% is the degradation rate of reactive black KN-B.
[0099] According to Lambert-Beer Law, when light passes through a solution, the solute molecules absorb the energy of the light, causing the intensity of the light to decrease. Therefore, in the solution of the dye reactive black KN-B, the concentration of reactive black KN-B is related to the absorbance value at 600nm (A 600 ). According to this principle, the linear relationship between the concentration of reactive black KN-B and the absorbance value was tested in the range of 0.2 to 15 mg / L (see Fig.11 ), its linear relationship expression is y = 0.035x-3.231, R 2 =0.999, and the concentration of reactive black KN-B in the solution was quantified using this linear relationship expression.
[0100] After the Pd / MMR used in Application Example 1 was washed with deionized water three times, the steps of Application Example 1 were repeated for a total of five cycles; after the Pt / MMR used in Application Example 4 was washed with deionized water three times, the steps of Application Example 4 were repeated for a total of five cycles. The comparison of the degradation rates of Pd / MMR and Pt / MMR after each cycle is shown in Fig.14 .
[0101] The degradation efficiency of the first cycle is recorded as 100%. After five cycles, the efficiencies of Pd / MMR and Pt / MMR are 95.64% and 96.47% of the first degradation efficiency, respectively. This shows that the catalyst prepared by the present invention has good recycling performance and can reduce the use cost of the catalyst to a certain extent through repeated use.
[0102] As can be seen from the above embodiments, the present invention provides a biomass-loaded metal nanocomposite catalyst and its preparation method and application, wherein the biomass material and polyethyleneimine solution are first mixed and incubated, and then a glutaraldehyde solution is added for cross-linking polymerization to obtain a modified biomass material; the modified biomass material is then added to a metal salt solution for adsorption to obtain a biomass material loaded with metal ions; and finally the biomass material loaded with metal ions is dispersed in a reducing agent solution for reduction reaction to obtain a biomass-loaded metal nanocomposite catalyst. The biomass-loaded metal nanocomposite catalyst prepared by the present invention has an excellent degradation effect on azo dye reactive black KN-B, and the degradation rate can reach 100% under acidic conditions.
[0103] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a biomass-supported metal nanocomposite catalyst, characterized in that: The steps include: (1) mixing a biomass material and a polyethyleneimine solution and incubating the mixture, and then adding a glutaraldehyde solution for cross-linking polymerization to obtain a modified biomass material; (2) adding the modified biomass material to a metal salt solution for adsorption to obtain a biomass material loaded with metal ions; (3) The biomass material loaded with metal ions is dispersed in a reducing agent solution to carry out a reduction reaction, thereby obtaining a biomass loaded metal nanocomposite catalyst.
2. The method for preparing a biomass-supported metal nanocomposite catalyst according to claim 1, characterized in that: In the step (1), the mass ratio of the biomass material to the polyethyleneimine solution is 1 g:80-120 mL, wherein the mass concentration of the polyethyleneimine solution is 3%-10%.
3. The method for preparing a biomass-supported metal nanocomposite catalyst according to claim 2, characterized in that: In the step (1), the incubation temperature is 25 to 35° C., and the incubation time is 6 to 30 hours.
4. The method for preparing a biomass-supported metal nanocomposite catalyst according to any one of claims 1 to 3, characterized in that: In the step (1), the mass ratio of the biomass material to the glutaraldehyde solution is 1:3-10, wherein the mass concentration of the glutaraldehyde solution is 5%-50%; the temperature of the cross-linking polymerization is 25-35° C., and the time of the cross-linking polymerization is 1-3 hours.
5. The method for preparing a biomass-supported metal nanocomposite catalyst according to claim 4, characterized in that: In the step (2), the metal salt in the metal salt solution comprises one or more of copper salt, iron salt, nickel salt, cobalt salt, gold salt, platinum salt, palladium salt and cerium salt; the concentration of the metal salt solution is 50 to 1000 mg / L; the adsorption time is 4 to 8 hours; The mass volume ratio of the modified biomass material and the metal salt solution is 20-40 mg:10-1000 mL.
6. The method for preparing a biomass-supported metal nanocomposite catalyst according to claim 2, 3 or 5, characterized in that: In the step (2), the reducing agent comprises one or more of sodium formate, sodium acetate, sodium borohydride, sodium sulfite and sodium thiosulfate; the concentration of the reducing agent solution is 1 to 50 mmol / L; the reduction reaction time is 10 to 180 min; The mass volume ratio of the modified biomass material and the reducing agent solution is 20-40 mg:10-1000 mL.
7. The biomass-supported metal nanocomposite catalyst prepared by the method for preparing the biomass-supported metal nanocomposite catalyst according to any one of claims 1 to 6.
8. Use of the biomass-supported metal nanocomposite catalyst in the degradation of azo dyes according to claim 7, characterized in that: The method comprises the following steps: mixing azo dye wastewater and biomass-loaded metal nanocomposite catalyst and reacting the mixture.
9. Use of the biomass-supported metal nanocomposite catalyst in the degradation of azo dyes according to claim 8, characterized in that: The concentration of azo dye in the azo dye wastewater is 5-50 mg / L; and the addition amount of the biomass-loaded metal nanocomposite catalyst is 0.1-1 g / L.
10. Use of the biomass-supported metal nanocomposite catalyst in the degradation of azo dyes according to claim 7 or 9, characterized in that: The reaction time is 10 to 60 minutes.